Ability of Tong Luo Jiu Nao Oral Solution to Improve Cognitive and Gait Deficits in a Rat Model of Focal Cerebral Ischemia - Si-Di Li (Digital Chinese Medicine, 2018)
ABSTRACT: Objective To investigate the ability of Tong Luo Jiu Nao (TLJN) Oral Solution to improve cognitive and gait deficits in a rat model of focal cerebral ischemia.Methods An intraluminal suture method was used to create a rat model of focal cerebral ischemia. Experimental animals were divided into 4 groups: sham surgery, cerebral ischemia model, cerebral ischemia model+low-dose TLJN Oral Solution (150 mg/kg), cerebral ischemia model + high-dose TLJN Oral Solution (300 mg/kg). After 4 weeks of drug intervention, water maze and gait analyses were conducted. Brain tissue was stained with hematoxylin and eosin and used to monitor and calculate the volume ratio of cerebral infarction in each group of permanent middle cerebral artery occlusion (pMCAO) rats.Results (1) Gait analyses: TLJN Oral Solution significantly improved the overall gait of the focal cerebral ischemic rat model. The improvement in walking speed might have been achieved by the shortening of the animals’ stride time. The shortening of stance time by TLJN in the cerebral ischemic animals might be due to the shortening of brake and propulsion times, while the shortening of stride time by TLJN in the cerebral ischemic animals might have been due to the shortening of stance time and swing time. (2) Water maze navigation test: high-dose TLJN Oral Solution significantly reduced the animals’ total swimming distance and duration and increased the proportion of swimming distance and time spent in the target quadrant, suggesting that TLJN significantly improved the cognitive deficit in the animal model. (3) High-dose TLJN significantly reduced the cerebral infarction volume ratio of the pMCAO rats.Conclusion This intraluminal suture method can reliably replicate a rat model of focal cerebral ischemia. TLJN Oral Solution improves the gait and cognitive function of the focal cerebral ischemia rat model to various extents. Keywords: Tong Luo Jiu Nao, Focal cerebral ischemia, Behavioristics, Gait analyses, Learning memory